Wintering destinations of Monterey Hermit Thrushes (Catharus guttatus slevini). Issue 1 (31st March 2021) - Nelson, Allison R. Paules; Wiskes, William T.; Seavy, Nathaniel E.
Abstract: Across their broad North American distribution, Hermit Thrushes ( Catharus guttatus ) exhibit extensive yet subtle intraspecific variation in morphology and diverse migration patterns, causing considerable debate regarding their systematics and an incomplete understanding of their migratory geography. To better understand the fall migration and wintering destinations of Hermit Thrushes in coastal California, we deployed geolocators on individuals of the subspecies C. g. slevini breeding in the Santa Cruz Mountains of the Coast Ranges. In 2014, we captured 20 Hermit Thrushes in Big Basin Redwoods State Park using mist‐nets and attached geolocators. In 2015, we retrieved tags from 13 birds. Tagged Hermit Thrushes left the breeding area between 1 and 19 September 2014 and arrived in wintering areas in Baja California Sur and northwestern mainland Mexico between 24 September and 13 October 2014. The average distance between breeding and wintering areas was 1617 ± 217 (SD) km, and the average duration of fall migration was 22.5 ± 6.4 (SD) days. Our results suggest that Hermit Thrushes breeding in Big Basin winter in a highly concentrated region of western Mexico including Baja California Sur and southwestern Sonora or northwestern‐most Sinaloa; we found no evidence that Big Basin birds overwintered in the southwestern United States. Our results also confirm the existence of chain migration for Hermit Thrushes in California. Because C. g. slevini exhibits a limited distribution in both breeding and wintering areas and their morphology and song suggest adaptation to their habitat, we recommend exploration of fine‐scale genetic structure of coastal California's Hermit Thrushes to determine the extent of evolutionary divergence in this subspecies. RESUMEN: Destinos de invierno de Catharus guttatus slevini A través de su amplia distribución en Norte América, Catharus guttatus muestra una amplia pero sutil variación intraespecífica en morfología y patrones de migración diversos, lo cual causa un debate considerable con respecto a su sistemática y una comprensión incompleta en la geografía de su migración. Con el fin de comprender mejor la migración de otoño y los destinos de invierno de C. guttatus en la costa de California, instalamos geolocalizadores en individuos de la subespecies C. g. slevini que se reproducen en las montañas de Santa Cruz de la Cordillera de la Costa. En 2014, capturamos 20 individuos de C. g. slevini en el parque estatal Big Basin Redwoods utilizando redes de niebla en los cuales instalamos geolocalizadores. En 2015, recuperamos los geolocalizadores de 13 aves. Individuos marcados abandonaron el área de reproducción entre el 1 y 19 de Septiembre de 2014 y llegaron a las áreas de invierno en Baja California del Sur y el área continental del noroeste de México entre el 24 de Septiembre y el 13 de Octubre de 2014. La distancia promedio entre las áreas de reproducción e invierno fue de 1617 ± 217 (DS) km, y la duración promedio de la migración de otoño fue de 22.5 ± 6.4 (DS) días. Nuestros resultados sugieren que la población de C. g. slevini que se reproduce en la región de Big Basin pasa el invierno en altas concentraciones en el oeste de México incluyendo el sur de Baja California y el suroeste de Sonora o la región mas al noroeste de Sinaloa; no encontramos evidencia que la población de Big Basin pasara el invierno en el Suroeste de Estados Unidos. Nuestros resultados también confirman la existencia de una migración en cadena en Catharus guttatus en California. Debido a que C. g. slevini muestra una distribución limitada, en las áreas de reproducción e invierno, y su morfología y canto sugieren adaptación al hábitat, recomendamos la exploración de la estructura genética a una escala fina de las poblaciones costeras de Catharus guttatus, con el fin de determinar el grado de divergencia evolutiva en esta subespecie.